Biosurfactants from commercially available bacillus spp. formulations: Production and evaluation as larvicides against aedes aegypti (L.) - Geron, Alfonso S. (Animo Repository, 2024)
Aedes aegypti (L.) is an insect vector of public health importance in the Philippines for its capability to transmit Dengue virus, Zika virus and Chikungunya virus. The use of biosurfactants produced from specific strains of Bacillus spp. that target larval and pupal stages is an emerging method for the biological control of mosquitoes. Here we evaluated commercially available formulations of Bacillus spp. (MagikGro and MagikKill) that have been previously used to control agricultural insect pests as a source of biosurfactants. Bacterial growth and biosurfactant production were monitored with OD600 readings and emulsion activity (E24), respectively. Highest biosurfactant production was observed after 24 h of incubation (log phase) in which highest E24 was recorded. Crude biosurfactant was isolated with acid precipitation and partially purified using alcohol precipitation. Larvicidal activity was determined using standard WHO protocols for testing larvicides. The biosurfactants from both formulations showed significant larvicidal activity even at the lowest concentrations tested: 97%and 100% mortality at 0.5 µg/mL for MagikGro and MagikKill, respectively. These results indicate that biosurfactants from these commercially available Bacillus spp. sources are viable alternatives for the biological control of Ae. aegypti.